Value-addition of methane via selective catalytic oxidation. Issue 2 (March 2014) - Karoshi, Gourishankar; Kolar, Praveen; Shah, Sanjay B; Gilleskie, Gary
Selective oxidation of methane into fuels and chemicals has attracted significant attention from researchers worldwide. However, because of its high stability, methane conversion involves multistep reactions. Hence, several catalytic approaches including homogeneous, heterogeneous biological and photocatalytic methods have been explored to selectively oxidize methane into methanol, and other chemicals such as ethane, ethylene and formaldehyde. The purpose of this Review is to discuss the current technologies and catalysts associated with selective oxidation of methane, reaction variables that influence selectivity and conversion, and challenges and available opportunities with methane conversion technologies. In addition, a few ideas to enhance the selectivity and conversion of methane are also presented.